Predicting the transport of 2,4-dinitroanisole (DNAN) and 3-nitro-1,2,4-triazol-5-one (NTO) in sandy and sandy loam soils - Gutierrez-Carazo, Encina; Dowle, James; Coulon, Frederic; Temple, Tracey; Ladyman, Melissa K. (Elsevier, 2022)
There is a trend toward the use of Insensitive High Explosives (IHE) in both military and civil applications as they are intended to be less prone to accidental detonation compared to traditional explosive fills. This has driven the development of new explosive formulations containing different chemical compounds whose behaviour once they are released into the environment is not fully understood. To date, research into the toxicity and the persistence of IHE compounds in the environment is scarce and little has been described about how they interact with, or move through soil. In this work, the transport of two IHE constituents, 2,4-dinitroanisole (DNAN) and 3-nitro-1,2,4-triazol-5-one (NTO), through two soil types (sand and sandy loam) was simulated in GoldSim using a stochastic approach. The simulation outputs were validated by comparison to results from empirical soil column experiments. Sorption of the IHE constituents to the soil was the most significant factor in predicting when the contaminants eluted from the soil column. Sensitivity analysis demonstrated that variation in the matrix water partition coefficient (Kd) had the greatest influence when used to predict the IHE compounds transport. Kd was measured empirically and, as expected, it was low in sand for NTO (0.334 L kg-1) and DNAN (0.401 L kg-1), suggesting high mobility. While in sandy loam Kd for NTO (0.242 L kg-1) was similar to one obtained in sand, it was significantly higher for DNAN (9.128 L kg-1), explaining the high retention and adsorption in the sandy loam soil. The use of stochastic modelling to estimate IHE breakthrough concentrations could enable the uncertainty inherent in environmental systems to be embedded into simulations, thus increasing their representativeness. This study is the first step toward proactive management of IHE in the environment, and may support decision making for remediation and mitigation strategies in different environments.
Keywords: Environmental impact; Insensitive High Explosives; soil contamination; GoldSim; Monte Carlo method